Association between obesity and mortality from hematological malignancies among Japanese adults: The Japan Collaborative Cohort study - Hana Wakasa; Satoshi Sunohara; Takashi Kimura; Takaya Ichikawa; Akiko Tamakoshi (PLoS ONE, 2025)
Obesity is a growing global health concern and has been associated with increased mortality from various cancer types, including hematological malignancies. However, evidence for this association in Asian populations, particularly among Japanese adults, remains limited. Thus, this study aimed to examine the association between obesity and mortality due to hematological malignancies. Data from 97,073 participants in the Japan Collaborative Cohort (JACC) Study were analyzed. The participants were followed for a mean duration of 17 years. Body mass index (BMI) was calculated using self-reported height and weight and categorized as underweight (<18.5 kg/m²), normal-weight (18.5–24.9 kg/m²), overweight (25.0–29.9 kg/m²), and obesity (≥30.0 kg/m²). Mortality data for hematological malignancies were obtained from death certificates. Cause-specific hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox proportional hazards models, with adjustments made for demographic, lifestyle, and socioeconomic factors. During follow-up, 479 died from hematological malignancies, including lymphoma (n = 200), multiple myeloma (n = 107), and leukemia (n = 166; 106 myeloid leukemia). Compared with normal-weight individuals, those classified as obese exhibited a significantly higher risk of mortality from all hematological malignancies (HR: 1.78; 95% CI: 1.02–3.11), multiple myeloma (HR: 2.75; 95% CI: 1.09–6.94), leukemia (HR: 2.47; 95% CI: 1.07–5.69), and particularly myeloid leukemia (HR: 3.89; 95% CI: 1.66–9.11). No significant association was observed between BMI and lymphoma-related mortality. Obesity is significantly associated with increased mortality from multiple myeloma and leukemia, especially myeloid leukemia, in Japanese adults. These findings underscore the importance of obesity as a modifiable risk factor for certain hematological malignancies in this population.